Exploring IT Companies in Taiwan Through Budget and Expert Capability - Yen, Chi Lung; Chou, Wen Shu (International Journal of Information Systems and Technology, 2025)
Creating an Information System is important for reaching the aims of implementing Electronic Government (E-Government). The Taiwanese government has decided to use outsourcing as a method for developing these Information Systems. In 2014, sixty percent of the Information Technology (IT) budget allocated to the Taiwanese government was used for the upkeep and management of the information systems created by external companies. The skills of IT staff and how the budget is distributed in a government agency can affect how the information system functions. Nevertheless, there is not much research available on this topic. This preliminary study employed direct observation and detailed interviews to examine an information system within a specific agency of the Taiwanese government. The findings indicated that although the IT staff possessed adequate technical skills, their exclusion from the system's development led to a lack of understanding of its technical specifics, which diminished their ability to operate and manage the system effectively. Additionally, the limited budget prioritized operational costs over system improvements. The insufficient technical understanding of the system not only affected its normal functioning but also made it challenging to create adequate budgets for the IT department. This study offers practical solutions and suggestions for future research.